2005
DOI: 10.1073/pnas.0507975102
|View full text |Cite
|
Sign up to set email alerts
|

Preferential occupancy of histone variant H2AZ at inactive promoters influences local histone modifications and chromatin remodeling

Abstract: The yeast histone variant H2AZ (Htz1) is implicated in transcription activation, prevention of the ectopic spread of heterochromatin, and genome integrity. Our genome-wide localization analysis revealed that Htz1 is widely, but nonrandomly, distributed throughout the genome in an SWR1-dependent manner. We found that Htz1 is enriched in intergenic regions compared with coding regions. Its occupancy is inversely proportional to transcription rates and the enrichment of the RNA polymerase II under different growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
233
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(262 citation statements)
references
References 35 publications
25
233
0
2
Order By: Relevance
“…Htz1 has a role in transcription and can also act as a barrier inhibiting spread of silent telomeric and mating locus heterochromatin into transcriptionally active regions. SWR1 dependent deposition of Htz1 was observed at telomeres (which requires Yaf9 component) [119], centromeres [120] and other intergenic regions [121]. Biochemical analyses have shown that Swc2 component binds Htz1 physically and is needed for Htz1 deposition [122].…”
Section: Ino80 and Swr1 Familymentioning
confidence: 99%
“…Htz1 has a role in transcription and can also act as a barrier inhibiting spread of silent telomeric and mating locus heterochromatin into transcriptionally active regions. SWR1 dependent deposition of Htz1 was observed at telomeres (which requires Yaf9 component) [119], centromeres [120] and other intergenic regions [121]. Biochemical analyses have shown that Swc2 component binds Htz1 physically and is needed for Htz1 deposition [122].…”
Section: Ino80 and Swr1 Familymentioning
confidence: 99%
“…H2ABbd is the smallest H2A variant, has a distinct N terminus, and is excluded from the Xi chromosome in mammalian cells [Chadwick and Willard, 2001]. H2A.Z and H2A.X are minor H2A variants that appear constitutively expressed and localize throughout the genome, although H2A.Z shows some enrichment in intergenic regions [Li et al, 2005]. Interestingly, the major H2A proteins in Saccharomyces cerevisiae and Schizosaccharomyces pombe are more similar to the mammalian H2A.X variant than the major mammalian H2A subtypes [Malik and Henikoff, 2003].…”
Section: Histone H2a Variantsmentioning
confidence: 99%
“…Results from yeast (Weiner et al 2010;Xi et al 2011;Kubik et al 2015), plants (Vera et al 2014), mouse (Lombraña et al 2013;Deng et al 2015;Iwafuchi-Doi et al 2016;Mieczkowski et al 2016), worm (Ooi et al 2010), and fly (Henikoff et al 2009; have identified highly labile nucleosomes in 5 ′ and 3 ′ "nucleosome-free" regions. In yeast, Xi et al (2011) observed that fragile nucleosomes were associated with H2A.Z-containing promoter nucleosomes, believed to be involved in stress response (Li et al 2005;Zhang et al 2005). In vertebrates, individual nucleosomes containing both H3.3 and H2A.Z histone variants are unstable (Jin and Felsenfeld 2007;Jin et al 2009).…”
Section: Mnase-resistant Nucleosomes Tend To Be In Gene Bodies and Comentioning
confidence: 99%